Preparing nurses to support cancer patients — preliminary report - Cepuch, Grażyna; Tomaszek, Lucyna; Wojtas, Katarzyna (Nursing Problems / Problemy Pielęgniarstwa, 2015)
Introduction. Social support provided by a nursing team to cancer patients together with the team competence plays an important role in the process of diagnosis, treatment and recovery. Aim of the paper. The aim of this study was the assessment of the extent of social support provided by nurses to cancer patients and their emotional burdens and expectations in terms of expanding the competence in this area. Material and methods. The study used the Berlin Social Support Scale and a questionnaire to assess the support provided by nurses. The study was conducted among 192 nurses working on oncology wards. For statistical calculations chi2 test or Fisher’s, Kruskala-Wallis’s, Manna-Whitney’s test was used. Results. Working with the oncological patients causes a considerable psycho-emotional burden — 95% nurses. The nurses (68%) feel competent to provide support, despite the deficits of knowledge in this area. Age and experience are factors determining the scope of support (informative support — p = 0.024; buffering-protective p = 0.045). Nurses (88%) recognize the need for further training. Conclusions. Competent support should be base in a good theoretical and practical knowledge of the nursing team. Nursing Topics 2015; 23 (4): 433–438